Teacher Strategies Applying Religious Modernation Values To The Islamic Religious Education Learning Process At SMPN 19 Singkawang City - Masruraini; Syahruddin Usman; Abdul Rahman Sakka; Hifza (IJGIE (International Journal of Graduate of Islamic Education), 2025)
The purpose of this study is to examine how teachers at SMPN 19 Singkawang City apply religious moderation principles in the Islamic Religious Education curriculum. A key component of fostering tolerance, appreciating diversity, and averting radicalism in the classroom is religious moderation. The socio-religious educational approach is the scientific technique used in this study, which takes a qualitative approach using the phenomenology method as its methodological approach. The study's findings show that teachers employ a scientific approach, group projects, discussions, and other techniques to promote religious moderation norm character development programs and role models. In addition, the role of teachers as role models is a key factor in building an understanding of religious moderation for students. The obstacles faced include limited student understanding of the concept of moderation and external influences that can affect their attitudes. Thus, effective strategies in implementing religious moderation values ​​can help create a harmonious and inclusive educational environment. This study is expected to contribute to curriculum development and improve teacher competence in instilling religious moderation values ​​in students.